Influence of Ice on the Bacteriological Quality of the Processed Fishery Products - IYER, T. S. GOPALAKRISHNA; CHOUDHURI, D. R. (Fishery Technology, 1966)
The influence of ice on the bacteriological quality of the processed fishery products has been discussed. In almost all the cases ice has been traced to be a major source of contamination depending on the nature of water used for preparing it. The sources of contamination of ice and its remedies have been described.